ALMA Study of the Lensed Galaxy SDP.81 - Azeez, Jazeel H; Fadhil, Sadeem Abbas; Naser-Alla, Zainab K.; Abidin, Zamri Z (Al-Nahrain Journal of Science, 2018)
In this paper we present high resolution data from Atacama Large Millimeter /sub-millimeter Array (ALMA) of CO (5-4) and CO (8-7) rotational transitions toward the gravitational lensed galaxy (SDP.81). We calculate the molecular gas mass in the clumpy region which is around 1.5´109 Mʘ. We overly the CO(8- 7) and CO(5- 4) intensity distributions to calculate the brightness temperature ratio R85 at various region. The CO line ratio was in the range between 0.39 and 0.75 with an average value about 0.48. This line ratio suggests that most sub-millimeter galaxies, SMGs, include a significant proportion of extended, moderate-density, cool gas.